Heparin promotes platelet responsiveness by potentiating αIIbβ3-mediated outside-in signaling - Gao, Cunji (American Society of Hematology, 2011)
Unfractionated heparin (UFH) is a widely used anticoagulant that has long been known to potentiate platelet responses to subthreshold doses of platelet agonists. UFH has been reported to bind and induce modest conformational changes in the major platelet integrin, αIIbβ3, and induce minor changes in platelet morphology. The mechanism by which UFH elicits these platelet-activating effects, however, is not well understood. We found that both human and murine platelets exposed to UFH, either in solution or immobilized onto artificial surfaces, underwent biochemical and morphologic changes indicative of a potentiated state, including phosphorylation of key cytosolic signaling molecules and cytoskeletal changes leading to cell spreading. Low molecular weight heparin and the synthetic pentasaccharide, fondaparinux, had similar platelet-potentiating effects. Human or mouse platelets lacking functional integrin αIIbβ3 complexes and human platelets pretreated with the fibrinogen receptor antagonists eptifibatide or abciximab failed to become potentiated by heparin, demonstrating that heparin promotes platelet responsiveness via its ability to initiate αIIbβ3-mediated outside-in signaling. Taken together, these data provide novel insights into the mechanism by which platelets become activated after exposure to heparin and heparin-coated surfaces, and suggest that currently used glycoprotein IIb-IIIa inhibitors may be effective inhibitors of nonimmune forms of heparin-induced platelet activation.